WUJUD ZAT DAN PERUBAHANNYA - Fatimah Azzahra; Aprila Nabila (JURNAL ILMIAH NUSANTARA, 2025)
There are six main ways matter can change state, such as melting (solid to liquid), freezing (liquid to solid), evaporation (liquid to gas), condensation (gas to liquid), sublimation (solid to gas), and crystallization or solidification (gas directly to solid). This study took place in class VI D, room 206 of the Elementary School Teacher Training Program at STKIP Al Maksum Langkat. The results obtained from this study indicate that the greater the number of milliliters of water, the longer the freezing time. The greater the number of milliliters of water, the longer the melting time. The greater the number of milliliters of water, the longer the evaporation time. The greater the number of milliliters of water, the higher the dew point value. The greater the amount of camphor, the longer the sublimation time, and the length of the crystallization process depends on the room temperature.